BRAND PREFERENCE OF NAGPUR’S FEMALE CONSUMERS TOWARDS COSMETIC & PERSONAL CARE PRODUCTS - Sondagar (Waghela), Poonam; Puniyani, Hariom J. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In recent years, the Cosmetic & Personal Care Product (C & PCP) market has experienced significant diversification, driven by the entry of numerous brands. The market has undergone a transformative shift, catalyzed by the rise in e-commerce platforms, increased accessibility to international products, and the emergence of homegrown brands committing to offering chemical-free, natural, and safe product alternatives. Positive post-COVID-19 effects proved to be the turning point for the substantial growth of the various brands entering the market with their different USPs catering to the diverse needs of Indian consumers. With so many brands flooding the market, consumers have ample choices for each category of Cosmetic and Personal Care Products (C & PCPs). The present research specifically focuses on discovering at the ground level which brands female consumers of Nagpur City prefer to choose from largely available alternatives. The researcher gathered data from 426 respondents from Nagpur using a structured questionnaire and a convenient random sampling method. The questionnaire also contained open-ended questions that allowed the respondents to mention their specific preferred brands other than the given options.